Efeitos da microgeometria de brocas helicoidais de metal duro na furação a seco de ferro fundido nodular GGG-50 - Tusset, Felipe (2015)
This study evaluated the effects of micro geomety in tool life and types of wear occurring in solid carbide drills, applied in dry drilling nodular cast iron GGG-50, as an alternative to reduce the process costs and increase the production capacity. The elimination of coolant in drilling processes imposes difficulty in chip extraction, loss of lubricity and the tool cooling effect, among others. These aspects have directly influence the tool life of cutting tools, to achieve this, make necessary changes in the macro and micro geometry the edge, which aim to reduce the effects caused by lack of lubrication and coolant, reinforcing the edge of the tool and prolonging its life . Treatment of rounding the cutting edge of the cutting tools provide better interaction between the tool and the material of the workpiece, promoting and enhancing micro geometry positive effect on tool life. Under this approach, experimental tests were performed with three types of micro geometries (R842, AGB2-R and AGB2-S) and two types of coating (AlCrN and TiNAl). The analyzes were monitored tool life of each condition, the wear mechanism and the micro geometry the effect of wear on these tools. The results indicated a 56% increase in cutting speed of 12% in feed for dry drilling process, compared to the usual parameters with application of coolant flood. The survey also revealed that for applications in extreme severity, micro geometry the tool edge need suffering a rounding treatment to support different efforts and unusual working conditions.